Validitas dan Praktikalitas Modul Reaksi Oksidasi Reduksi Berbasis Inkuiri Terbimbing Dilengkapi Soal High Order Thinking Skill (HOTS) untuk Siswa Kelas X SMA/MA - Yvonne Rodiana Bahri; Iryani Iryani (Universitas Negeri Padang, 2020)
This research aims to determine the category of validity and practicality of module based on guided inquiry on redox reaction with high order thinking skill’s question (HOTS) for 10th grade students. This research uses a research design of the Plomp model development which consist of 3 phases: preliminary research, prototyping phase, assessment phase. The data were analysed using kappa moment. This module is validated by 5 validators that consisting of 3 chemistry lecture and 2 chemistry teacher who are experienced and experts in their fields. The result of this research showed that the module had a high category of validity with a kappa moment of 0,77. The module has a high category of practicality based on the teacher’s questionnaire responses which has a kappa moment of 0.80 and the module practicality category based on student questionnaires is equal to 0.70.